2005
DOI: 10.1063/1.1935046
|View full text |Cite
|
Sign up to set email alerts
|

NO and NO2 production in pulsed low pressure dc discharge

Abstract: Simultaneous measurements of both NO and NO2 are performed downstream a pulsed low pressure dc discharge in flowing air using tunable diode laser absorption spectroscopy in the infrared region. Pulse duration and repetition rate range from 20 μs to 5 ms and from 50 to 1000 Hz, respectively. The gas pressure is 4 mbar and the peak current is 80 mA. Experimental results show that NO and NO2 production depends only on the duty cycle ratio, that is, on the average power at a given current. A numerical computation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 14 publications
5
25
0
Order By: Relevance
“…According to Rousseau et al NO and NO 2 generation depends “only on the duty cycle ratio” [23]. The Duty Cycle Ratio (DCR) is defined as the ratio of the pulse duration to the pulse period.…”
Section: Resultsmentioning
confidence: 99%
“…According to Rousseau et al NO and NO 2 generation depends “only on the duty cycle ratio” [23]. The Duty Cycle Ratio (DCR) is defined as the ratio of the pulse duration to the pulse period.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the electronically excited state of nitrogen, N 2 (A), has been recognized in the recent decades as a significant contributor to thermospheric NO production through owing to its long radiative lifetime in the low‐pressure environment in the thermosphere (Gatilova et al, ; Guerra et al, ; Ionikh et al, ; Kutasi et al, ; Loureiro et al, ; Ono & Oda, ; Pintassilgo et al, ; Rousseau et al, ). N2()A+normalO()normalP3NO+normalN()normalD2 …”
Section: No Chemistry In the Thermospherementioning
confidence: 99%
“…An important update to the NO photochemistry here is the inclusion of the electronically excited state of nitrogen, N 2 (A), as an additional source of NO (Gatilova et al, 2007;Guerra et al, 2001;Ionikh et al, 2006;Kutasi et al, 2007;Loureiro et al, 2011;Ono & Oda, 2002;Pintassilgo et al, 2009;Rousseau et al, 2005), implemented as suggested by Yonker (2013). An in-depth discussion of our current understanding of NO photochemistry in the context of a 1-D model can be found in Yonker (2013).…”
Section: Introductionmentioning
confidence: 99%
“…The existence of a nitric oxide (NO) channel from the reaction of N 2 ( A ) with ground state atomic oxygen O ( 3 P ) has been repeatedly invoked to explain the NO present in the postdischarge region of a laboratory N 2 /O 2 plasma (Gatilova et al, ; Guerra et al, ; Ionikh et al, ; Kutasi et al, ; Loureiro et al, ; Ono & Oda, ; Pintassilgo et al, ; Rousseau et al, ). As a primary thermospheric cooling mechanism (Mlynczak et al, ), ozone destroyer (Randall et al, ), and ionospheric component (Nicolet, ), a new source of NO, if significant, will have important consequences for many upper atmospheric processes.…”
Section: Introductionmentioning
confidence: 99%